Reviewing the Human Capital Performance Stimulants of Employees In Logistic Transportation with a Quantitative Approach - Alkistasari, Intan; Harianto, Eric (Jurnal Entrepreneur dan Entrepreneurship, 2022)
This study aims to determine the effect of work discipline, work environment, and organizational culture on job satisfaction and employee performance in logistics transportation companies. This study uses a sampling technique that is saturated sample. The population used in this study were all employees of PT. Surya Lintas Abadi, totaling 56 people. This research was conducted from May 2021 to December 2021. This research method is quantitative with data collection using questionnaires. The analytical method used is Partial Least Square (PLS). The results of this study are work discipline has an effect on job satisfaction, work environment has an effect on job satisfaction, organizational culture has an effect on job satisfaction, job satisfaction has an effect on employee performance, work discipline has no effect on employee performance, work environment has an effect on employee performance, organizational culture has an effect on employee performance. Of the seven existing hypotheses, the biggest influence is the effect of work discipline on job satisfaction.PT. Surya Lintas Abadi can increase employee satisfaction by making employees have time discipline. The hypothesis that has no effect is the effect of work discipline on employee performance .PT. Surya Lintas Abadi needs to implement a key performance index as a tool to make it easier to assess and evaluate employee performance.